In vitro EVALUATION OF TWO DRUGS OF VETERINARY USE AGAINST PATHOGENS CAUSING OTITIS EXTERNA IN DOGS - Gutiérrez R., Luz Adriana (2014)
The aim of this study was to evaluate the in vitro effect of two drugs of frequent use in veterinary practice against microorganisms isolated after treatment in 27 dogs with otitis externa. Various isolates were obtained from five dogs: two Pseudomonas aeruginosa, three Staphylococcus intermedius, and three yeasts of the genus Malassezia. The level of effectiveness of the antimicrobial drugs was determined by the method of Minimum Inhibitory Concentration (MIC). Gentamicin (3 mg/ml) and clotrimazole (10 mg/ml) solutions were prepared. Bacteria and yeast were brought to a concentration of 1x106 microorganism/ml. In ELISA plates, 150 μl of each bacteria or yeast and 150 μl of gentamicin or clotrimazole was added. Two repetitions and three replicates of each microorganism were considered in the study. As controls, drugs plus water and microorganisms plus water were used, and the volume adjusted to 300 μl each. Growth conditions in the spectrophotometer were 35 °C/10 rpm/24 h, where the growth kinetics of the microorganisms were measured at 660 OD. Results showed that gentamicin at a dose of 3 mg/ml causes an adequate growth inhibition of the bacteria, whereas clotrimazole can be used in the case of otitis caused by yeasts (M. pachidermatis), but at concentrations above 14 mg/ml.